2015
DOI: 10.1039/c5ra17969f
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted acid-catalyzed selective C–C bond cleavage of 1,3-diketones: a facile synthesis of 4(3H)-quinazolinones in aqueous ethyl lactate

Abstract: A facile and green approach was developed for the synthesis of 4(3H)-quinazolinones by using camphorsulfonic acid as a catalyst in an aqueous solution of biodegradable ethyl lactate. Various 2-aryl-, 2alkyl-, and 2-(4-oxoalkyl)quinazolinones were obtained by cyclization of 2-aminobenzamides with a wide range of acyclic or cyclic 1,3-diketones via C-C bond cleavage in satisfactory-to-excellent yields. Scheme 1. A green approach to 4(3H)-quinazolinones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Uozumi and co-workers showed that camphorsulfonic acid (CSA) can be used as efficient catalyst for the synthesis of 4( 3H )-quinazolinones [ 161 ]. The reaction used a water-ethyl lactate mixture as green solvent and was able to produce the desired compounds from a large variety of 2-aminobenzamides and 1,3-diketones (Scheme 70 ).…”
Section: Synthetic Applications In Homogeneous Systemsmentioning
confidence: 99%
“…Uozumi and co-workers showed that camphorsulfonic acid (CSA) can be used as efficient catalyst for the synthesis of 4( 3H )-quinazolinones [ 161 ]. The reaction used a water-ethyl lactate mixture as green solvent and was able to produce the desired compounds from a large variety of 2-aminobenzamides and 1,3-diketones (Scheme 70 ).…”
Section: Synthetic Applications In Homogeneous Systemsmentioning
confidence: 99%
“…12 In 2019, Tang & Pan's group developed an electrochemical cross-dehydrogenation coupling to construct CN double bonds for the synthesis of rutaecarpine alkaloids (Scheme 2b). 13 To continue our interest in ether/O 2 promoted oxidative cleavage, 8 N -heterocyclic synthesis, 14 and green organic synthesis, 15 we report here an intramolecular oxidative dehydrogenative coupling for the construction of dihydroisoquinolino[2,1- a ]quinazolinones, 2-aryl quinazolinones, and analogues promoted by bis(2-methoxyethyl)ether in the presence of molecular oxygen under clean conditions (Scheme 2c).…”
Section: Introductionmentioning
confidence: 99%
“…[3] It also has been fruitfully engaged in the extraction of various bioactive compounds and diverse food such as carotenoids, [4] polyphenols, [5] amino acids [6] and caffeine. [7] Besides, it has successfully being employed as a green solvent in a number of effective organic reactions [8] for the preparation of significant compounds such as spirooxindole-pyran derivatives, [9] 1,4-benzothiazines, [10] bis(Indolyl)methanes, [11] polyfunctionalized alkenes, [12] quinoxalines, [13] 4(3H)-quinazolinones, [14] 2-pyrazoline derivatives [15] and enaminones. [16] For a long period, aromatic azo-compound has received considerable amount of interest among the chemists.…”
Section: Introductionmentioning
confidence: 99%